Respuesta agronómica y rendimiento de frutos de los Pepinos Híbridos ‘diamante’ y ‘amanda’ a la aplicación de diferentes niveles de fertilización química - Ezeta Flores, Héctor Hugo (2014)
This research was conducted in the grounds of the Farm 'San Pablo' , belonging to the Faculty of Agricultural Sciences , Technical University of Babahoyo , located on 7.5 km of track Babahoyo - Montalvo, Rivers Province ; testing hybrid cucumbers 'Diamante' and ' Amanda ' in the presence of chemical fertilization levels : 0 - 0 - 0 ; 60 - 30 - 70; 120 - 50 - 130 and 180 - 70-190 kg / ha of nitrogen, phosphorus and potassium , in order to: a) evaluate the agronomic performance of hybrid cucumbers in the presence of different nutritional levels; b ) Identify the appropriate nutritional level to maximize fruit yield per hectare; c ) Determine the agronomic efficiency of hybrid cucumbers according to nutritional standards; d ) Analyze the economic fruit yield according to the production cost of the treatments.